The Influence of Using Green Marketing on Intention to Purchase Environmentally Friendly Products - Luwy Berto Marbun; Rizky Pramudita Bukit; Sanusi Gazali Pane (Journal of Education Technology Information Social Sciences and Health, 2024)
Currently, there is increasing environmental damage throughout the world. One of the factors causing environmental damage is global warming. Issues regarding the environment are a problem that is being highlighted by the wider community. The problem of air pollution, water pollution, and the most phenomenal is the problem of waste. Green marketing is an activity carried out by companies that pay attention to the environment or green issues by providing environmental goods or services to create satisfaction, developing products with a positive impact on the environment whose production, use and disposal processes do not have a detrimental effect on the environment, product sales results used for environmental purposes. The aim of this research is to determine the influence of the use of green marketing and consumer trust on the intention to purchase environmentally friendly products. The method used in this research is a quantitative descriptive survey method, namely by giving online questionnaires to respondents. This online questionnaire is aimed at respondents who use environmentally friendly products. The results in this research show how far the independent variable partially influences the dependent variable. From the results of the partial (t) test, it can be concluded that hypothesis (X2) Consumer trust influences consumer purchase intentions (Y) towards environmentally friendly products.